Avaliação dos efeitos de doses sub-anestésicas de cetamina sobre o medo condicionado à luz em ratos - Magalhães, Mylena Silva (Universidade Federal de São Carlos, 2021)
Fear and anxiety play a key role in ensuring survival. Both are adaptive reactions that organisms exhibit in response to threatening situations. Although they are adaptive, they can become clinically relevant and turn out on anxiety disorders. The pharmacological treatments commonly used for these disorders increase anxiety symptoms in the initial therapeutic phase, a characteristic that can make treatment adherence difficult. The glutamatergic system plays a central role in aversive conditioning and the pathogenesis of anxiety. Thus, pharmacological agents capable of modulating this neurotransmission can be effective for the treatment of anxiety-related disorders. Recent studies have shown that ketamine, an antagonist of the N-methyl-D-aspartate (NMDA) receptor, has the potential to act on anxiety symptoms quickly and effectively when administered in sub-anesthetic doses. The objective of this work was to evaluate the potential effects of ketamine, at different doses and times of administration, on the acquisition, consolidation, expression, and extinction of conditioned fear. For this, 192 male Wistar rats were used. Ketamine was administered intraperitoneally, at doses of 0, 10, 20 and 30 mg/kg. The drug was administered 30 minutes before training (experiment 1), immediately after training (experiment 2), 30 minutes before the test (experiment 3) or immediately after the test (experiment 4). Ketamine at a dose of 30 mg/kg, administered 30 minutes before training, attenuated the freezing response in the training session and in the following test and retest sessions, 24 and 48 hours after training. The same effect was not observed for the 10 mg/kg or 20 mg/kg doses. Ketamine administered immediately after fear conditioning training had no significant effect on the following test and retest sessions. The administration of ketamine at doses of 20 mg/kg and 30 mg/kg, 30 minutes before the test, impaired extinction, an effect observed in the retest session. Finally, ketamine administered immediately after the test session did not alter freezing in the retest session. Overall, these results indicate that ketamine interferes with the processing of aversive memories and, consequently, with the behavioral expression of fear. Both dose and timing of administration appear to be important factors in the effects of ketamine on conditioned fear. Additional studies are needed to replicate the findings of the present study and to investigate molecular processes underlying the effects of ketamine on aversive memory acquisition and extinction.
Evaluation of the effects of sub-anesthetic doses of ketamine on cued fear conditioning in rats
Keywords: Cetamina; Congelamento; Condicionamento aversivo clássico; Ansiedade; Extinção; Ketamine; Freezing; Classic aversive conditioning; Anxiety; Acquisition; Extiction; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::ESTADOS SUBJETIVOS E EMOCAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::PSICOBIOLOGIA